O direito fundamental da saúde do trabalhador e a quantificação do adicional de insalubridade - Gonçalves, Daniel Itokazu (2011)
The life and health of the worker is being study object for a time, especially because of the considerable number of work accidents that occur around the world. Thus, increases the constant concern of international agencies, as OMS and OIT, in giving concreteness to the various forms of protection to the worker. If, in the past, the Man had to adapt himself to the work, in subhuman conditions, which had its peek on the Industrial Revolution, today, there is necessity of the work conditions to be adapted to the Man on the capitalist way of production, in which the worker is incepted as a part of the productive process and fundamental element in the work organization. Despite the fact of the Health have the status and valor of a Fundamental Right, deserving a specific care, the Estate is far from providing a real protection, especially when is analyzed the health/life of the ones constantly exposed to the harmful effects of the of the unhealthy agents. The way found to resolve this question it was the Monetary Reparability to whom works in unhealthy environments and are exposed above the tolerance limits of the human organism, that consists in a additional that will vary conform the intensity of the exposition to the unhealthy agent. However, what was, in the beginning ,considered the solution to such problems (arising from the social conquests), tends to collapse, in now days, behind the actual needs of workers, because the risk monetization, utilized until today in Brazil, is considered outdated as a form to protect the worker , once the monetary gain is not able to repair the health wasted. Also, the social costs of those workers victims of workplace accidents cannot be denied. They are removed from their labor to health care or die from the occupational diseases, in a real overcharge of the Social Pension directly, which is responsible for granting the benefits, and, indirectly, of the whole society. Giving this situation, it is clear that everyone loses with the lack of preventive measures about the environmental unhealthy, because the onus falls over the worker, who suffers the occupational disease, over the employer, who suffers the lack of a worker and still had to pay more tributes that covers the cost of the Social Pension, and over the society, that had to collaborate with this cost too. Even if is true that the Estate had good will in trying to minimize the high taxes of accidents creating a tribute called Accident Preventive Factor, whose mechanism consists in a bonus to the companies with lower level of accidents in media and a onus to the ones with higher level; it´s valid the questioning about if the law that created the tribute offends or not the reserve of law and about the real intentions from the Estate, the tribute was created as it was said or had only inflow purposes. There are examples in the world about the adoption of alternative measures, like the reduced journey to who works in unhealthy environments and the prohibition of extra hours, also there is the extended ferias in the same conditions. However, the today discussions in this area still are appointed as dispensable by the doctrine, as can be understandable in the Súmula Vinculante nº 4 and the TST´s Súmula nº 228: both treats only the base of calculation of the unhealthy additional, ignoring the conditions of the human dignity. In this case, the problem is indicate that the modern monetizing criterion is not promoting the dignity of the worker, having in mind the fact that his health is increasingly threatened, starting by the stiffening of the regulation promoted by the Ministry of Work and Employ, because only is considered unhealthy when the work appears in the NR-15, not mattering the existence of technical report in contrary sense. So, is clear the necessity of a more effective presence of the Estate in promoting the Health of the worker, not only conceiving fiscal incentives to the companies with lower levels of accidents, but also, as a form of punishing to the recalcitrant, making them invest in the workplace environment seeking to diminish or even vanishing the unhealthy agents effects, because, although the alarming indices of work hazards, the doctrine alerts about the unreality of the statistics due the cheats, called hazard subnotification , many of them doesn´t appear in the total compute. Therefore, urges a political and juridical modification to be overcome the stuffiness that still dominates the Brazilian scene in the area of occupational health, in which the Estate itself serves as a bad example when turns a blind eye to the degradation of the workplace environment in its policy of growth economical acceleration.